A Critical Discourse Analysis on the Representation of Rape among Sudanese Women on Al-Jazeera.Net - Aprilia, Lulu Eka; Al Anshory, Abdul Muntaqim (SUAR BETANG, 2024)
Global media attention has focused on the protracted conflict between the Sudan Armed Forces and the Rapid Support Forces in the Sudanese region. This war has led to an alarming increase in violations of women's rights, particularly cases of violence against women. This research aims to examine and reveal the positions of subjects and objects, as well as the portrayal of rape perpetrators in Al Jazeera news. The research method employed is qualitative descriptive analysis. Data sources are derived from the Al Jazeera portal broadcasted on August 16, 2023, with the page titled "hurriyyaat”. The data collection technique involves reading and note-taking. Data analysis utilizes presentation techniques, analysis, and drawing conclusions based on Sara Mills' perspective. The research findings indicate that the subject's position is that of a woman and a victim, while the object is the perpetrator of rape. In this article, the news writer demonstrates bias towards rape victims, with the dominant portrayal of women as readers aimed at providing sympathetic support and empathy for women who have experienced violent events such as rape. AbstrakPerhatian media dunia fokus kepada konflik yang berlarut-larut antara pasukan Sudan Armed Force dan pasukan pendukung cepat di wilayah Sudan. Perang tersebut menyebabkan peningkatan pelanggaran yang mengkhawatirkan dalam kasus kekerasan terhadap perempuan. Penelitian ini bertujuan mengkaji dan mengungkap posisi subjek-objek dan penulis pembaca pemerkosaan dalam berita Al-Jazeera. Metode penelitian yang digunakan adalah deskriptif kualitatif. Sumber data berasal dari portal Al-Jazeera yang ditayangkan pada 16 Agustus 2023 di halaman hurriyyaat. Teknik pengumpulan data yang digunakan ialah teknik baca dan catat. Adapun analisis data menggunakan teknik penyajian data, analisis, dan penarikan simpulan berdasarkan perspektif Sara Mills. Adapun hasil penelitian menunjukkan bahwa posisi subjek adalah perempuan sekaligus korban dan objeknya adalah pelaku pemerkosaan. Dalam artikel ini, penulis berita menunjukkan keberpihakan pada korban pemerkosaan, sedangkan dominan perempuan sebagai pembaca ditampilkan untuk memberi dukungan simpati dan empati pada perempuan yang mengalami peristiwa kekerasan seperti pemerkosaan.